PERTUNJUKAN SENI BADUT DAN PAKAIAN ADAT BUDAYA PADA OBYEK WISATA ISTANA BASA PAGARUYUNG - Misda Elina; Leni Efendi; Efrinon Efrinon (PROSIDING: SENI, TEKNOLOGI, DAN MASYARAKAT, 2019)
The research aims to describe the art and cultural performances at the tourism of BasaPagaruyung Palace. These two factors can provide a different experience compared to other regions as tourist destinations of the BasaPagaruyung Palace. The research uses descriptive methods with an analysis of democratic government with the people adhering matrilineal system. Performing arts and leasing of Minangkabau traditional clothing become a tourist attraction at the BasaPagaruyung Palace. This research is important and urgent because in the context of the tourism industry, in addition to the main attraction of a tourist destination, complementary attraction provides a different experience from each region visited by tourists. The results of the study show that the arts and cultural performances at the tourist sites of the Palace of BasaPagaruyung are performances of clown art and rental of Minangkabau traditional clothing which is a complementary attraction that is different from the attraction of tourist destinations elsewhere, due to the design of clown shows and clothing rentals that is designed according to the traditional Minangkabau characteristics. It makes clown performances and rental of Minangkabau traditional costumes provide a different experience with other regions for tourists visiting the tourist sites of the BasaPagaruyung Palace.